Hubungan Antara Pola Asuh Orang Tua Dengan Motivasi Belajar Siswa Selama Transisi Pasca Pandemi - Della Nathaniel Gea (Jurnal Ilmu Pendidikan Guru Sekolah Dasar dan Usia Dini, 2026)
This study aims to examine the relationship between parenting styles and students’ learning motivation during the post-pandemic transition period. The shift from online to face-to-face learning has created various challenges in students’ adaptation processes, particularly in terms of learning motivation. This research employed a quantitative approach with a correlational method. The sample consisted of 80 junior and senior high school students selected using purposive sampling techniques. Data were collected through a questionnaire using a Likert scale that had been tested for validity and reliability. Data analysis was conducted using descriptive statistics and Pearson Product Moment correlation analysis. The results showed that democratic parenting was the most commonly applied parenting style. Additionally, students’ learning motivation was generally categorized as moderate to high. The correlation analysis indicated a significant and positive relationship between parenting styles and students’ learning motivation, with a correlation coefficient of 0.62. This finding implies that better parenting styles are associated with higher levels of students’ learning motivation. This study highlights the important role of parents in supporting students’ learning processes, especially during the post-pandemic transition period.